Nucleosomal chromatin in the mature sperm of Drosophila melanogaster - Abdul Hakim Elnfati; David Iles; David Miller (Genomics Data, 2016)
During spermiogenesis in mammals and many other vertebrate classes, histone-containing nucleosomes are replaced by protamine toroids, which can repackage chromatin at a 10 to 20-fold higher density than in a typical somatic nucleus. However, recent evidence suggests that sperm of many species, including human and mouse retain a small compartment of nucleosomal chromatin, particularly near genes important for embryogenesis. As in mammals, spermiogenesis in the fruit fly, Drosophila melanogaster has also been shown to undergo a programmed substitution of nucleosomes with protamine-like proteins. Using chromatin immunoprecipitation (ChIP) and whole-genome tiling array hybridization (ChIP-chip), supported by immunocytochemical evidence, we show that in a manner analogous to nucleosomal chromatin retention in mammalian spermatozoa, distinct domains packaged by the canonical histones H2A, H2B, H3 and H4 are present in the fly sperm nucleus. We also find evidence for the retention of nucleosomes with specific histone H3 trimethylation marks characteristic of chromatin repression (H3K9me3, H3K27me3) and active transcription (H3K36me3).Raw and processed data from the experiments are available at GEO, accession GSE52165.